Dakota - Lajiness, Katie (2019)
This title introduces readers to the Dakota people and covers traditional ways of life, including social structure, homes, food, art, clothing, and more. Also discussed is contact with Europeans and American settlers, as well as how the people keep their culture alive today.
Amazing people -- Dakota territory -- Home life -- What they ate -- Daily life -- Made by hand -- Spirit life -- Storytellers -- Fighting for land -- Back in time -- The Dakota today.
Includes index.
Ages 7-10
Keywords: Dakota Indians -- Juvenile literature; Dakota Indians; Juvenile works